The historical-sociological matrix and ethos at the heart and strength of MPLA’s modern Angola - Vidal, N. C. de F. (Tempo, 2019)
Proximate to a Weberian perspective, this article argues that the resilience of the Angolan regime is mainly owed to an ethos structured on top of a specific socio-cultural historical matrix (minority at start), evolving since the 16th century. Such matrix was structured on a prevailing Weltanschauung (world and national vision), that has been progressively self-presented, self-assumed, imposed/assimilated as national and modern within a project of identity and power hegemony, even though still and constantly ridden by several internal contradictions and tensions. Dynamics of this process is central to understand the intricacies of the relationship between rulers and ruled, evolving identities as well as the still significant social support to the party in power after more than four decades in the government. The regime’s resilience lays on such ethos in support of hegemonic power and identity project, above and beyond the president and all his political management abilities, beyond the central instrumentality of the national oil company (SONANGOL), beyond the media spotlight on influential names surrounding the presidency, including the president’s men, generals, and beyond authoritarianism.